Conformally invariant differential operators and bilinear functionals in six dimensions - Ugalde, William J. (2008)
We review how to construct the Paneitz operator in dimension four and the corresponding operator in dimension six, by constructing symmetric bilinear differential functionals that are conformally invariant.